IMPLEMENTASI VIRTUAL REALITY DALAM PEMBELAJARAN PENGOLAHAN HASIL PERTANIAN UNTUK MENCIPTAKAN SUASANA YANG REALISTIS DI SMKN 3 TAKALAR - Noviana Safitri; Jamaluddin; Hartini Ramli; Akmal Hidayat; Muh. Fadli Syafar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The advancement of digital technology in the field of education has encouraged the adoption of various innovative learning media capable of providing more interactive and engaging learning experiences while bringing students closer to real-life situations. One of the technologies with significant potential to support the learning process is Virtual Reality (VR), which enables students to gain learning experiences through immersive simulations of virtual environments. This study aims to analyze students’ responses to the use of Virtual Reality media and to examine the effectiveness of its implementation in creating a realistic learning environment in the Agricultural Product Processing subject for Grade XI students of the Agribusiness of Agricultural Product Processing (APHP) program at SMKN 3 Takalar. This research employed an experimental method conducted at SMKN 3 Takalar. The population consisted of all students enrolled in the Agribusiness of Agricultural Product Processing (APHP) program, while the research sample included 22 Grade XI APHP students who were divided into an experimental group and a control group. Data collection was conducted by administering closed-ended questionnaires using a Likert scale to students in both research groups. The findings revealed that the implementation of Virtual Reality media was more effective than expository learning in supporting the creation of a realistic learning environment. This was demonstrated by the questionnaire results, in which the experimental group achieved percentages ranging from 59% to 82%, while the control group obtained assessment percentages ranging from 50% to 73%. Based on these findings, the use of Virtual Reality had a positive impact, both in terms of its utilization as a learning medium and its ability to create a more realistic learning environment. Nevertheless, further development and refinement are still necessary to ensure that the application of Virtual Reality technology in the learning process can be utilized more effectively and adapted to the characteristics and needs of students.